The Baltimore Fund : investor meeting in Baltimore - Rosenberg, Carin, (SAGE knowledge. Cases., 2016)
Patrice McConnell Cromwell, Program Development Fellow of the Open Society Institute (OSI), prepared her notes for her 9:00 am meeting. Investors of the Baltimore Fund would soon be gathering in OSI's Baltimore, Maryland office to hear the latest financial and workforce development report from the Fund's investment manager. As she fathered her notes, Cromwell reflected on the major challenges the group had faced since April 2001 when they had initiated work on the fund. Getting the Fund off the ground had not been easy. To meet billionaire George Soros' challenge of securing $10 million in funds from at least two other sources, Cromwell and her colleagues had turned to private sector institutions as well as small and large foundations in the Baltimore region. This case study discusses this topic.